Role of toll-like receptors in post-COVID-19 associated neurodegenerative disorders? - Satyanarayanan, Senthil Kumaran; Yip, Tsz Fung; Han, Zixu; Zhu, Huachen; Qin, Dajiang; Lee, Suki Man Yan (Frontiers in Medicine, 2025)
In the intricate realm of interactions between hosts and pathogens, Toll-like receptors (TLRs), which play a crucial role in the innate immune response, possess the ability to identify specific molecular signatures. This includes components originating from pathogens such as SARS-CoV-2, as well as the resulting damage-associated molecular patterns (DAMPs), the endogenous molecules released after cellular damage. A developing perspective suggests that TLRs play a central role in neuroinflammation, a fundamental factor in neurodegenerative conditions like Alzheimer’s and Parkinson’s disease (PD). This comprehensive review consolidates current research investigating the potential interplay between TLRs, their signaling mechanisms, and the processes of neurodegeneration following SARS-CoV-2 infection with an aim to elucidate the involvement of TLRs in the long-term neurological complications of COVID-19 and explore the potential of targeting TLRs as a means of implementing intervention strategies for the prevention or treatment of COVID-19-associated long-term brain outcomes.